2020
DOI: 10.1055/a-1016-8813
|View full text |Cite
|
Sign up to set email alerts
|

Interventionelle Echokardiografie

Abstract: ZusammenfassungDie interventionelle Echokardiografie (also Echokardiografie während der Herzkatheterintervention) hilft, Strukturen zu visualisieren, die in der Fluoroskopie nicht oder nur schlecht sichtbar sind und erlaubt die Überprüfung der Behandlungsergebnisse vor Abschluss der Prozedur am „schlagenden Herzen“. Am Beispiel der Edge-to-Edge-Rekonstruktion mittels MitraClip lässt sich gut zeigen, dass die Echokardiografie bereits bei der Erfassung der Morphologie bzw. Anatomie eine entscheidende Rolle für d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…They noted that elevated procalcitonin levels were associated with poorer prognosis and correlated with the degree of atherosclerosis in coronary artery disease. In a similar study, Sinning et al 16 reported that initial elevated procalcitonin levels were associated with cardiovascular events and higher mortality during follow-up.…”
Section: Discussionmentioning
confidence: 86%
“…They noted that elevated procalcitonin levels were associated with poorer prognosis and correlated with the degree of atherosclerosis in coronary artery disease. In a similar study, Sinning et al 16 reported that initial elevated procalcitonin levels were associated with cardiovascular events and higher mortality during follow-up.…”
Section: Discussionmentioning
confidence: 86%